2023
DOI: 10.1186/s13045-023-01454-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cachexia: molecular mechanisms and treatment strategies

Abstract: Muscle wasting is a consequence of physiological changes or a pathology characterized by increased catabolic activity that leads to progressive loss of skeletal muscle mass and strength. Numerous diseases, including cancer, organ failure, infection, and aging-associated diseases, are associated with muscle wasting. Cancer cachexia is a multifactorial syndrome characterized by loss of skeletal muscle mass, with or without the loss of fat mass, resulting in functional impairment and reduced quality of life. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 301 publications
0
14
0
5
Order By: Relevance
“…The SwissTargetPrediction tool was used to determine the human targets of selected phytocompounds, and canonical SMILES were given as an input ( , accessed on 21 August 2023) [ 92 ]. In addition, 238 reported cachexia-associated genes were collected through a literature survey and web search for manual comparative analysis to find the unique genes [ 93 , 94 , 95 , 96 ]. The list of cachexia-associated genes collected is given in Supplementary Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“…The SwissTargetPrediction tool was used to determine the human targets of selected phytocompounds, and canonical SMILES were given as an input ( , accessed on 21 August 2023) [ 92 ]. In addition, 238 reported cachexia-associated genes were collected through a literature survey and web search for manual comparative analysis to find the unique genes [ 93 , 94 , 95 , 96 ]. The list of cachexia-associated genes collected is given in Supplementary Table S3 .…”
Section: Methodsmentioning
confidence: 99%
“… 19 While early explanations for the weight loss seen in patients with cancer was attributed to inadequate caloric intake, research has revealed that cachexia is in fact a complex systemic disease, characterized by tumor–host interactions, metabolic aberrations that result in negative energy balance, increased lean muscle proteolysis and adipose lipolysis, and neurohormonal dysregulation. 20 , 21 …”
Section: Pathophysiological Perspectivementioning
confidence: 99%
“…Cytokines are regulatory proteins released by cells of the immune system and act asintercellular mediators in the generation of an immune response. 21 Upregulation of proinflammatory cytokines are implicated in altered metabolism and increased energy expenditure. Studies have demonstrated disturbances in REE in cancer patients such that even at rest, compared to healthy controls, cancer patients have increased rates of REE.…”
Section: Pathophysiological Perspectivementioning
confidence: 99%
“…Cachexia refers to a phenomenon in which despite the intake of sufficient calories, there is a decrease in body weight, loss of appetite, or an imbalance in effects. The metabolic changes triggered by cancer cachexia, such as autophagy, elevated energy expenditure, nutrient sequestration by tumors, and proteolysis, collectively result in reduced oxidative capacity of cardiac muscle, disrupted mitochondrial homeostasis, and muscle atrophy, ultimately culminating in weight loss [ 1 ]. Cancer cachexia is multifactorial and cannot be fully reversed by nutritional support.…”
Section: Introductionmentioning
confidence: 99%